A segurança do trabalho nas coletas de solo em agricultura de precisão - Giraldi, Caroline Montanari (2023)
Brazilian agribusiness is an important factor for the country's economic growth. The sector is also responsible for generating a large number of jobs. Precision agriculture (PA) presents itself as an efficient tool to reduce the use of resources, making agricultural production increasingly competitive. One of the main methods for efficient management in AP is georeferenced soil sampling, which, if performed using instrumented ATVs and/or motorcycles, makes the work more agile, minimizing service time and worker effort. The modernization and mechanization of agriculture has brought more and more efficiency in the agricultural process, but it has also brought an increase in the number of accidents in rural work. The present study aimed to carry out a survey with companies that provide services in PA, on work safety in this environment. For this, a qualitative exploratory research was used through a questionnaire, prepared by the Google Forms platform and sent virtually to the members of the Brazilian Association of Service Providers in Precision Agriculture. The study had the participation of 38 companies. The results showed that the quadricycle is the most used means of transportation for soil collection. The profile of the worker who performs this activity is from a technical training course aged between 25 and 29 years. Regarding Occupational Safety, the companies participating in the survey have or contract outsourced services on the subject, indicating that there is a concern for the health of their employees. With regard to Occupational Safety training, greater adherence may still occur, given that some employees have never participated in specific courses on the subject. When the question was about the occurrence of the Internal Week for the Prevention of Accidents at Work (SIPAT), it is noticed that there is a high number of companies that need to pay greater attention to the subject, since in 57.9% of the companies SIPAT took place. As for the use of Personal Protective Equipment (PPE), there is awareness and concern on the part of companies with the health and safety of employees, and that PPE is provided. Even though it is not mandatory, some companies already use ATVs with a front protection grid and awning, providing greater safety for the operator. As for accidents during soil collection, what happens most frequently is the ATV overturning, followed by fire or the beginning of a fire in the ATV or field and the operator falling. When asked about what would be the main causes of accidents in soil collection, two main answers were obtained: terrain obstacles, and the operator's lack of attention during work. In short, the AP sector still needs to evolve with regard to the classification of workers in the sector, and to give more approach to training in Occupational Safety, especially including SIPAT. It is noteworthy that studies in the area of rural work safety, especially in AP need to be more emphasized, increasingly valuing the health and safety of workers.